Folium reservatum : [being a supplement to O-kee-pa: a religious ceremony; and other customs of the Mandans]. - Catlin, George, 1796-1872 (s.n., 1867)
As the publishing standards of the time did not permit a complete description of the O-kee-pa ceremony, Catlin compiled a separate "Folium reservatum" to detail the more shocking elements.